From spatial experience to the area of a paper: physical activity to overcompensate SLD - Lovecchio, Nicola; La Torre, Antonio; Della Vedova, Naike (Formazione & insegnamento, 2018)
The handwriting is a complex ability resulting from a series of motor pathways to link letters and arrange the words (on the same line) following specific rules. This specific ability required an high level of motor control and a fine modulation of muscles strenght: low level of general coordination and accuracy in motor control negatively affect the writing outcomes. Thus, the dysgraphia is recognised as typical motor impairment. In the present study, analysed the graphic deficit as a spatio-temporal process within a specific and closed area using the total-body experience. Some student with an official LSD diagnosis were involved in a specific gym protocol to improve the body/motor schemas, the perception of spatio-temporal coordinates and the eyeshand coordination. Indeed, the general purpose was to monitor a potential transfer between the total body spatial experience on the hand outcomes. The improvements in the handwriting outcomes revealed with an evidence practice approach a real possibility to overcompensate the dysgraphia in gym context.